2019
DOI: 10.1080/21645515.2019.1632684
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal influenza vaccination among health-care workers: the impact of different tailored programs in four University hospitals in Rome

Abstract: Seasonal influenza vaccination (SIV) of health-care workers (HCWs) is recommended in most countries to protect them and their patients from infection. Although SIV can reduce the risk of influenza complications among vulnerable patients, vaccination uptake is generally unsatisfactory. The present study aimed to assess the impact of different programs in promoting SIV uptake among HCWs during the season 2017/2018 in four teaching hospitals in Rome. A multicentric cross-sectional study was carried out, in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…In our study, 46.1% of the samples tested positive for the presence of influenza A and B viruses, with a greater prevalence of the former over the latter, as also reported in other European countries [18]. As expected, the highest peak of FLU A and B circulation was observed in the cold months (O.R.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, 46.1% of the samples tested positive for the presence of influenza A and B viruses, with a greater prevalence of the former over the latter, as also reported in other European countries [18]. As expected, the highest peak of FLU A and B circulation was observed in the cold months (O.R.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the overall vaccination coverage rate was lower than those reached in other international settings [22,27,29,51,52], thus remaining unsatisfactory and still far away by the minimum goal of 75% defined by the WHO and by the Italian PNPV (PNPV 2017-2019) [10,11]. However, the vaccination coverage registered in our teaching hospital represents an encouraging starting point and it is analogous, or even higher, than flu vaccination coverage rates registered in other national and regional settings [29,32,33,39,50,[53][54][55]. Our results confirmed that physicians are the professionals most willing to get vaccinated, as reported in the literature [20,33,50,54], even though the overall increase was the lowest during the considered period if compared to nurses and OHCWs.…”
Section: Discussionmentioning
confidence: 78%
“…It is therefore a starting point for planning effective vaccination campaigns [ 38 ]. In the literature, there are works that investigate knowledge and attitudes towards vaccination, mainly in parents and vaccinees [ 39 ]. There are also examples of training courses or interventions concerning vaccinations aimed at meeting the training needs of health workers and improving adherence to vaccinations by facilitating communication aspects.…”
Section: Discussionmentioning
confidence: 99%